2007
DOI: 10.1007/s11136-007-9215-3
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in breast cancer survivors two to five years post diagnosis: a HEAL Study report

Abstract: This study provides further support for the conclusion that a significant proportion of breast cancer survivors experience fatigue that compromises HRQOL two to five years post-diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
116
0
17

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 53 publications
(72 reference statements)
9
116
0
17
Order By: Relevance
“…First, antidepressant use in our cancer study population (27.7%) was similar to antidepressant use in previous studies (10% to 34%) [11,239,[255][256][257][258][259][260][261][262]. Specifically, in breast cancer patients, 34.4% used antidepressants, which is consistent with the maximum reported percentage of breast cancer patients using antidepressants in previous studies (11% to 34%) [11,239,[255][256][257][258][259][260][261].…”
Section: Strengthssupporting
confidence: 88%
See 2 more Smart Citations
“…First, antidepressant use in our cancer study population (27.7%) was similar to antidepressant use in previous studies (10% to 34%) [11,239,[255][256][257][258][259][260][261][262]. Specifically, in breast cancer patients, 34.4% used antidepressants, which is consistent with the maximum reported percentage of breast cancer patients using antidepressants in previous studies (11% to 34%) [11,239,[255][256][257][258][259][260][261].…”
Section: Strengthssupporting
confidence: 88%
“…Another study found antidepressants were self-reported in 27% of breast cancer patients; this percentage increased to 32% in patients with lymphedema [259]. At a 2-year interview, 15% of breast cancer patients reported taking an antidepressant [260], while another 2-year study found 19.2% of breast cancer patients were prescribed antidepressants [256]. Using a prescription database, among women taking tamoxifen who were older than 66, 30.6% were prescribed at least one SSRI or venlafaxine [261].…”
Section: Antidepressant Usementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies have confirmed that breast cancer survivors with increased fatigue rated their quality of life at a lower level [12][13][14]16 . On the other hand, assessing fatigue in cancer survivors is a challenge since fatigue is also a common complaint with some level of fatigue reported by the general population 17,18 .…”
Section: Introductionmentioning
confidence: 75%
“…Many studies suggest that fatigue is a common problem experienced by female survivors of breast cancer 6,[9][10][11][12][13][14][15] . Moreover, previous studies have confirmed that breast cancer survivors with increased fatigue rated their quality of life at a lower level [12][13][14]16 .…”
Section: Introductionmentioning
confidence: 99%